Kajian filsafat kurikulum merdeka: Kurikulum merdeka menurut perspektif filsafat aliran esensialisme & konstruktivisme - Sa’adah, Amanatus (Maliki Interdisciplinary Journal, 2024)
The curriculum that always follows the development of education in Indonesia is always adapted to the needs of the nation. The independent curriculum that is applied now is a prototype curriculum during the covid-19 period that has been refined. The method used in this research is library research, by collecting various sources of literature from various media, which are then analyzed and become a more relevant scientific work. The preparation of an independent curriculum is bound by the foundations of educational philosophy, namely the school of essentialism and the school of constructivism. Both schools have an important role in the preparation of an independent curriculum, because both have relevance to the needs that exist today.